EFFECT OF EMOTIONAL INTELLIGENCE AND ROLE CONFLICT ON LIFE SATISFACTION AMONG TEACHERS - Sharma, Gargi; Dhankar, Charu (International Journal of Psychosocial Rehabilitation, 2020)
21th century may be called competitive century because cut thought competition is changing the mindsets or priorities, values and norms of life. In this competitive century role and responsibilities is increasing day by day which may create role conflicts. This role conflicts influences the level of life satisfaction. The current piece of paper is an effort to know the effect of role conflicts and emotional intelligence on life satisfaction. The sample consists of 100 subjects (50:50 = males: females) working in teaching profession. The sample has taken from various governments. Both group were matched in term of professional qualification, age group and marital status. For assessing role conflict, emotional intelligence and life satisfaction ‘Teachers ‘Role- conflict Inventory, Emotional intelligence scale and life satisfaction tools were used respectively. To find out the impact of emotional intelligence and role conflicts on life satisfaction 2×2 factorial design is used. Result shows that there is a significant effect of emotional intelligence and role conflicts on life satisfaction.